THE ROLE OF INNOVATIVE PEDAGOGY IN TEACHING STUDENTS TO THINK CREATIVELY (World Bulletin of Social Sciences, 2021)
This article analyzes the role of innovative pedagogy in teaching students to think creatively. The author discusses the possibilities of innovative pedagogy